Avoidable injuries after intervention for abdominal aortic aneurysm: An analysis of negligence claims over 15 years in Sweden - David Bergqvist; Pelle Gustafson; Larsolof Hafström (Upsala Journal of Medical Sciences)
Background: Patients, who are subjected to a patient's injury, are legally allowed a compensation for their suffering. Aim: The negligence claims after surgical treatment of abdominal aortic aneurysms (AAA) registered in the National Swedish patient insurance company (Landstingens Ömsesidiga Försäkringsbolag [LÖF]) between 2006 and 2020 were analyzed. More than 95% of negligence claims are covered by LÖF. Special emphasis on avoidable or unavoidable injuries was made. Material: In 15 years 17,000 abdominal aortic interventions were recorded in the Swedish vascular register (SWEDVASC), where vascular interventions in the whole country of Sweden are registered. A total of 151 negligence claims (0.9%) were reported to the insurance company. Available clinical information in the company’s file of the claims was analyzed. The SWEDVASC data on AAA treatment were accessible. Results: The number of Endovascular repair (EVAR) increased significantly, but the total number of interventions decreased. There were less claims after EVAR (0.7%) compared to open surgery (1.1%). There was an increase in avoidable injuries that were economically compensated (p = 0.02). Spinal cord ischemia and intestinal ischemia were dominating causes for claims Conclusion: The increase in the number of avoidable injuries should have an impact on how to train and support colleagues under education and efforts to diminish the injuries are essential. To develop methods to diminish the risk for non-avoidable complications is important.